The supplementation of L-carnitine in septic shock patients: Systematic review and meta-analysis - Guedes, Gabriel Voltani [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Tanni, Suzana Erico [UNESP] (Elsevier, 2022)
Background: Sepsis and septic shock are severe and difficult-to-treat conditions with high lethality. There is interest in identifying new adjunct therapies that are effective in reducing mortality. In this context, L-carnitine has been investigated in trials as a potentially beneficial drug. Therefore, the aim of this systematic review was to assess the clinical evidence to support the use of L-carnitine in septic shock patients to reduce the risk of mortality. The objective of this review was to evaluate the effect of L-carnitine compared to placebo or Usual Care (UC) on the mortality rate in hospitalized adult septic shock patients. Methods: The authors exclusively included randomized clinical trials that compared the use of L-carnitine versus placebo in adult (> 18 years old) septic shock patients. The outcome was a mortality rate of 28 days. This systematic review and meta-analysis were performed following the PRISMA guidelines and registered in PROSPERO with the ID CRD42020180499. Results: Following the initial search, 4007 citations were identified, with 2701 remaining after duplicate removal. Eight citations were selected for body text reading, and two were selected for inclusion. The studies enrolled 275 patients, with 186 in the carnitine arm and 89 in the placebo arm. The effect of L-carnitine uses in septic shock patients showed a difference risk of -0.03 (95% Confidence Interval: -0.15–0.10, I2 = 77%, p = 0.69) compared to placebo/in mortality rate with low quality of evidence. Conclusions: There is low-quality evidence that the use of L-carnitine has no significant effect on reducing 28-day mortality in septic shock patients.
Keywords: L-carnitine; Mitochondrial dysfunction; Mortality; Septic shock